Hubungan Dukungan Keluarga dan Pemanfaatan Herbal Medicine sebagai Upaya Preventif dengan Kepatuhan Pengobatan TB paru di Puskesmas Rawat Inap Sidomulyo - Arnila Melina; Octariany, Octariany; Dewi Murni Manihuruk; Fahmi Nofriandi (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Pulmonary tuberculosis (TB) remains a major public health problem in Indonesia. Despite the implementation of national TB control programs through the Directly Observed Treatment Shortcourse (DOTS) strategy, treatment success continues to face significant challenges, particularly related to patient adherence to anti-tuberculosis drug (ATD) therapy. Non-adherence to TB treatment can lead to treatment failure, disease relapse, and the development of drug-resistant tuberculosis, thereby increasing the overall burden of the disease.Treatment adherence in TB patients is influenced not only by medical factors but also by social and behavioral determinants. Family support plays a crucial role in encouraging patients to comply with treatment regimens by providing motivation, reminding medication schedules, and offering emotional support throughout the long duration of therapy. Patients who receive adequate family support tend to demonstrate higher levels of treatment adherence compared to those with limited support.In addition, the use of herbal medicine as a preventive and supportive health measure is common among the Indonesian population. Herbal medicine is often utilized to enhance immune function, reduce medication side effects, and improve patient comfort during TB treatment. However, the use of herbal remedies without proper medical guidance may lead to misconceptions regarding standard TB therapy.Therefore, it is important to examine the relationship between family support and the use of herbal medicine as preventive measures with treatment adherence among pulmonary TB patients in primary healthcare settings. Such evidence is expected to support a comprehensive family medicine approach and strengthen TB control programs in primary care services.